1999
DOI: 10.1101/gad.13.7.901
|View full text |Cite
|
Sign up to set email alerts
|

The RecBC enzyme loads RecA protein onto ssDNA asymmetrically and independently of chi , resulting in constitutive recombination activation

Abstract: Double-strand DNA break repair and homologous recombination in Escherichia coli proceed by the RecBCD pathway, which is regulated by cis-acting elements known as sites. A crucial feature of this regulation is the RecBCD enzyme-directed loading of RecA protein specifically onto the 3-terminal, -containing DNA strand. Here we show that RecBC enzyme (lacking the RecD subunit) loads RecA protein constitutively onto the 3-terminal DNA strand, with no requirement for . This strand is preferentially utilized in homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
123
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 62 publications
6
123
0
Order By: Relevance
“…This model is supported by the fact that recD mutants are recombination-proficient (11,23,29) and hyperre-combination-proficient in the absence of Chi sites (11), and they cluster recombination events at the ends of DNA in lambda replication-blocked crosses (30). Purified RecBC enzyme (i.e., lacking RecD) has a low affinity for dsDNA (unpublished data, see Table 5) ends but can unwind DNA (16,31,32) and facilitates loading of RecA protein at the 3Ј termini of DNA during unwinding (16). This is in contrast to RecBCD enzyme, which requires a Chi site for significant loading of RecA protein (6), joint molecule formation (7), and recombination (18).…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…This model is supported by the fact that recD mutants are recombination-proficient (11,23,29) and hyperre-combination-proficient in the absence of Chi sites (11), and they cluster recombination events at the ends of DNA in lambda replication-blocked crosses (30). Purified RecBC enzyme (i.e., lacking RecD) has a low affinity for dsDNA (unpublished data, see Table 5) ends but can unwind DNA (16,31,32) and facilitates loading of RecA protein at the 3Ј termini of DNA during unwinding (16). This is in contrast to RecBCD enzyme, which requires a Chi site for significant loading of RecA protein (6), joint molecule formation (7), and recombination (18).…”
mentioning
confidence: 71%
“…As a consequence of the RecBCD enzyme-Chi interaction, both the DNA substrate (4-7) and enzyme (8)(9)(10) are changed. Genetic and biochemical experiments have suggested that one or another RecBCD enzyme subunit directs this regulation (8,(11)(12)(13)(14)(15)(16). We show here that the RecD subunit inhibits E. coli recombination by blocking RecBCD enzyme-facilitated loading of RecA protein onto single-stranded (ss) DNA.…”
mentioning
confidence: 79%
See 3 more Smart Citations